The relationship between overweight and stress towards the premenstrual syndrome in undergraduate students of midwife education, Airlangga University - Kharisma, Binta Ulfatul; Dwiningsih, Sri Ratna; Al Farizi, Sofia (Science Midwifery, 2023)
Premenstrual syndrome is one of the menstrual disorders that appear 7-10 days before menstruation comes and can disappear during menstruation, but can also continue afterwards. Indonesian women who experience premenstrual syndrome (PMS) are 80-90%. Adolescents aged 18-21 years (44.5%) and 22-25 years (22.5%) experience moderate to severe PMS. The purpose of this study was to analyze the relationship between overweight and stress on the incidence of premenstrual syndrome in undergraduate midwifery education students at Airlangga University. This research used observational analytic study method with cross sectional approach. The population was 283 people with a sample size of 138 people conducted by purposive sampling. The independent variables in this study were overweight and stress, while the dependent variable was the incidence of premenstrual syndrome. The instruments in this study used the SPAF questionnaire, DASS-42, and BMI calculation using body weight and height. The data were analyzed using Spearman correlation with α = 0.05. The results of this study found that 32.6% of female students had overweight and obese BMI, 74% of female students experienced high to moderate stress, and 63% of female students experienced mild premenstrual syndrome. In the Spearman correlation test results, it was found that overweight and the incidence of premenstrual syndrome had a p value = 0.000 (p < 0.05) and the level of stress and the incidence of premenstrual syndrome with a p value = 0.000 (p < 0.05). There is an association between overweight and stress with the incidence of premenstrual syndrome (PMS).